Progressive Phosphorylation Modulates the Self-Association of a Variably Modified Histone H3 Peptide - Papamokos, George V.; Tziatzos, George; Papageorgiou, Dimitrios G.; Georgatos, Spyros; Kaxiras, Efthimios; Politou, Anastasia S. (Frontiers in Molecular Biosciences, 2021)
Protein phosphorylation is a key regulatory mechanism in eukaryotic cells. In the intrinsically disordered histone tails, phosphorylation is often a part of combinatorial post-translational modifications and an integral part of the “histone code” that regulates gene expression. Here, we study the association between two histone H3 tail peptides modified to different degrees, using fully atomistic molecular dynamics simulations. Assuming that the initial conformations are either a-helical or fully extended, we compare the propensity of the two peptides to associate with one another when both are unmodified, one modified and the other unmodified, or both modified. The simulations lead to the identification of distinct inter- and intramolecular interactions in the peptide dimer, highlighting a prominent role of a fine-tuned phosphorylation rheostat in peptide association. Progressive phosphorylation appears to modulate peptide charge, inducing strong and specific intermolecular interactions between the monomers, which do not result in the formation of amorphous or ordered aggregates, as documented by experimental evidence derived from Circular Dichroism and NMR spectroscopy. However, upon complete saturation of positive charges by phosphate groups, this effect is reversed: intramolecular interactions prevail and dimerization of zero-charge peptides is markedly reduced. These findings underscore the role of phosphorylation thresholds in the dynamics of intrinsically disordered proteins. Phosphorylation rheostats might account for the divergent effects of histone modifications on the modulation of chromatin structure.